Guide to U.S. health and health care policy - Oliver, Thomas R. (Gale virtual reference library, 2014)
"Guide to U.S. Health and Health Care Policy provides the analytical connections showing students how issues and actions are translated into public policies and institutions for resolving or managing healthcare issues and crises, such as the recent attempt to reform the national healthcare system. The Guide highlights the decision-making cycle that requires the cooperation of government, business, and an informed citizenry in order to achieve a comprehensive approach to advancing the nation's healthcare policies. Through 30 topical, operational, and relational essays, the book addresses the development of the U.S. health care system and policies, the federal agencies and public and private organizations that frame and administer those policies, and the challenges of balancing the nation's health care needs with the rising costs of medical research, cost-effective treatment, and adequate health insurance. This must-have reference for political science and public policy students who seek to understand the issues affecting health care policy in the U.S. is suitable for academic, public, high school, government, and professional libraries"--Provided by publisher